Endo‐wing versus transparent hood‐assisted colonoscopy for colorectal adenoma detection: A randomized controlled trial. Issue 4 (22nd February 2022) - Miyaguchi, Kazuya; Tsuzuki, Yoshikazu; Hirooka, Nobutaka; Shiomi, Rie; Ohgo, Hideki; Nakamoto, Hidetomo; Imaeda, Hiroyuki
Abstract: Background and Aim: This study aimed to compare the mean number of adenomas in patients undergoing Endo‐wing‐assisted colonoscopy (EAC) and transparent hood‐assisted colonoscopy (TAC). Methods: Patients undergoing colonoscopy for positive fecal immunochemical tests, colon polyp surveillance, and evaluation of abdominal symptoms at a single institution were randomly assigned to the EAC or TAC group. The mean number of adenomas per patient, adenoma detection rate, cecal intubation time, withdrawal time, mean number of adenomas per location, and adenoma size were compared. Results: Overall, 800 patients were enrolled. The EAC and TAC groups comprised 372 and 393 patients, respectively. The groups did not significantly differ with respect to cecal intubation and withdrawal times. The mean number of adenomas per patient was significantly higher in the EAC group (1.13 vs 0.90, P  = 0.04), particularly in the sigmoid colon (0.54 [201/372] vs 0.38 [149/393], P  = 0.04). The adenoma detection rates were 48.1% and 45.0% in the EAC and TAC groups, respectively, albeit without significant difference between the two groups ( P  = 0.393). The total number of sessile‐type adenomas (0.73 [270/372] vs 0.47 [183/393], P  < 0.0001) and small polyps (≤ 5 mm) (0.53 [198/372] vs 0.41 [159/393], P  = 0.016) was significantly higher in the EAC group. Conclusion: Endo‐wing‐assisted colonoscopy is significantly superior to TAC in terms of the mean number of adenomas per patient.